Treatment outcomes of nasopharyngeal carcinoma in modern era after intensity modulated radiotherapy (IMRT) in Hong Kong: A report of 3328 patients (HKNPCSG 1301 study). (February 2018) - Au, K.H.; Ngan, Roger K.C.; Ng, Alice W.Y.; Poon, Darren M.C.; Ng, W.T.; Yuen, K.T.; Lee, Victor H.F.; Tung, Stewart Y.; Chan, Anthony T.C.; Sze, Henry C.K.; Cheng, Ashley C.K.; Lee, Anne W.M.; et al.
Highlights: Treatment outcomes of 3328 NPC patient treated with IMRT in Hong Kong. 8 year local/regional control remained promising. Confirmed benefits of concurrent chemotherapy with IMRT. Additional chemotherapy onto backbone of concurrent chemo-irradiation warrants further investigation. Various severe symptomatic complications after IMRT remained low. Abstract: Purpose: To evaluate treatment outcomes, failure patterns and late toxicities in patients with nasopharyngeal carcinoma (NPC) treated by intensity modulated radiotherapy (IMRT) in 6 public hospitals in Hong Kong over a 10-year period from 2001 to 2010. Material and methods: Eligible patients were identified through the Hong Kong Cancer Registry data base. Clinical information was retrieved and verified by oncologists working in the individual centers. Treatment details, survival outcomes and late toxicities were analyzed. Results: A total of 3328 patients were recruited. The median follow-up time was 80.2 months. The 8-year actuarial overall survival (OS), local failure-free survival (LFFS), regional failure-free survival (RFFS), distant failure free survival (DFFS), progression-free survival (PFS) for the whole group was 68.5%, 85.8%, 91.5%, 81.5% and 62.6% respectively. Male gender, older age, advanced T and N stage were adverse prognostic factors for OS, DFFS and PFS, whereas use of chemotherapy in form of concurrent chemo-irradiation (CRT), neoadjuvant + CRT, or CRT + adjuvant chemotherapy were favorable prognostic factors for OS and PFS. The local control was adversely affected by advanced T stage. N stage remained as the single adverse prognostic factor for regional control. Distant metastasis was the commonest site of failure. Conclusion: IMRT is an effective treatment for NPC with excellent overall loco-regional control. Distant metastasis is the major site of failure. Concurrent chemotherapy with cisplatin has an established role in NPC patients treated by IMRT.